Perencanaan Strategis Sistem Informasi Penjualan Jasa Pada CV. XYZ Dengan Metode Analisa SWOT - Dwi Remawati (STMIK Sinar Nusantara, 2013)
Strategic Planning Information System (PSSI) is a process to identify a computer-based portfolio that will help the organization in carrying out its business plans and realizing its business goals, on the contrary PSSI can also generate demand for applications with high leverage and ability to create excellence among its competitors. Analysis of the situation and the ongoing business functions, such as an analysis of five competitive forces and SWOT analysis.Information Systems Strategic Planning the sale of services on the CV. XYZ have targets to support management functions within the company, particularly in the areas of customer service and management services. With this strategic planning, information needs for good leadership for materials planning, organization, assessment, control and decision-making and information needs of customers are expected to be met. Strategic planning which will be developed based on the priority activities that must be implemented according the company's goals.Key word :Information System, Strategic Planning, SWOT analysis, sale of services